Business study mission to Latin America tourism sector in Argentina, Chile and Peru. - Berliana Ali. (2008)
This report is part of a study mission conducted by the School of Accountancy and Business Administrations of the Nanyang Technological University. The Business Study Mission was performed in December 1998. The purpose of the mission was to provide first hand observations of business practices in different cultural and political environments. It also helps to improve the interregional understanding and relationship, as well as to promote economic investment.